Factors associated with body mass index and health-related quality of life among high school students in Tehran - Jalalifarahani, Sara (2013)
This cross-sectional study was conducted to determine factors associated with body mass index-for-age (BMI-for-age) and health-related quality of life (HRQOL) among high school students in Tehran. A total of 465 high school students (227 girls and 238 boys) aged between 14 to 17 years old and their parents who were residing in Tehran, participated in this study. Body weight and height of the students were measured by trained researchers. Body weight status (BMI-for-age) was determined using world health organization growth standard (WHO 2007). The students completed a set of self-administered student-version questionnaire that assessed HRQOL, dietary practices, body image and physical activity of the students. In addition, the students were interviewed by researcher on their dietary intake using two 24-hour dietary recalls. Besides, a self-administered parent-version questionnaire that comprised socio-demographic information, self-reported parental body weight and height, parental perception of student body weight status and parental perception of student HRQOL were completed by parent of the students. Based on the WHO Growth standard (2007), the prevalence of overweight and obesity was higher than thinness. The highest and the lowest subscale scores of HRQOL were reported in social functioning and emotional functioning subscales respectively. BMI-for-age of the students was significantly associated with BMI of mother, BMI of father, parental perception of student’s body weight status, parental perception of student’s HRQOL, total daily intakes of energy, carbohydrate and protein, meal skipping, disordered eating, body image and physical activity. On the other hand, BMI-for-age of the students was not significantly associated with age and gender of student, marital status of parent, working status of mother, occupation of father, number of year of education completed by parents, snacking, eating companion, daily hours of sleeping and daily hours of screen time viewing. The HRQOL of students was significantly associated with gender of student, BMI of mother, BMI of father, parental perception of student’s body weight status, parental perception of student’s HRQOL, total daily intakes of energy, carbohydrate and protein, meal skipping, eating companion, disordered eating, body image and daily energy expenditure. On the other hand, the HRQOL of the students was not significantly associated with age of student, marital status of parent, working status of mother, occupation of father, number of year of education completed by parents, snacking, physical activity, daily hours of sleeping and daily hours of screen time viewing. BMI-for-age was inversely and significantly correlated with HRQOL. The one-way ANOVA indicated that mean of HRQOL total score was significantly different by body weight status. Normal weight students had better HRQOL compared with both overweight and obese students. There was no significant difference in HRQOL between thin and normal weight students. Result of multiple linear regression analysis showed that negative body image, low level of physical activity, high energy intake and high parental BMI were factors which significantly contributed towards high BMI-for-age in high school students in Tehran. Body image, physical activity level, energy intake and parental BMI explained 54.9% of variances in BMI-for-age model. Among these factors, body image was the strongest factor that could explain 38.3% of the variation in BMI-for-age model. Further, multiple linear regression analysis showed that poor parental perception of student HRQOL, negative body image, being female, being overweight and obese, not having eating companion, low level of daily energy expenditure and incorrect parental perception of student body weight status significantly contributed towards poor HRQOL in high school students in Tehran. In addition, 57.7% of variances in HRQOL model were explained by parental perception of student HRQOL, body image, gender of student, overweight-obesity, eating companion status, daily energy expenditure and parental perception of student body weight status. Among these factors, parental perception of student HRQOL was the strongest factor that could explain of 45.4% of the variation in HRQOL model.Hence, intervention programs should incorporate factors associated with BMI-for-age in the current study to overcome overweight and obesity problem in high school students of Tehran. Moreover, factors associated with HRQOL of students should be included in intervention programs to improve HRQOL of high school students in Tehran. Attention should be focused on body image since negative body image contributed to high BMI-for-age and poor HRQOL in high school students in Tehran. Considering parental influences on both BMI-for-age and HRQOL regression models, parents should be involved in future intervention programs that aim to combat overweight-obesity and improving HRQOL of high school students in Tehran.